(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2012)
The limekiln which is the subject of this paper was found during the last excavation in Gortys (2010), conducted by the University of Milan in the so called “Terme Milano”, south of the Pretorio. The little limekiln, which probably dates between the end of the 6th century A.D. and the beginning of the 7th century A.D., was set after the great bath complex had collapsed for one of the strong earthquakes that struck Gortys in those times. As the sizes are modest, the kiln is suggested to be a periodic one, used for a short period, but in close connections with some new byzantine constructions and accomodations in the Pretorio area. The paper is also a reconsideration of the evidence on other limekilns in Gortys (in the theater of Pythion, in Byzantine Quarter ecc.) and in Crete (the great kiln in Aptera) at the end of the classical time.